Multiwavelength observations of nova SMCN 2016-10a – one of the brightest novae ever observed. Issue 2 (14th October 2017) - Aydi, E; Page, K L; Kuin, N P M; Darnley, M J; Walter, F M; Mróz, P; Buckley, D A H; Mohamed, S; Whitelock, P; Woudt, P; Williams, S C; Orio, M; et al.
Abstract: We report on multiwavelength observations of nova Small Magellanic Cloud Nova 2016-10a. The present observational set is one of the most comprehensive for any nova in the Small Magellanic Cloud, including low-, medium-, and high-resolution optical spectroscopy and spectropolarimetry from Southern African Large Telescope, Folded Low-Order Yte-Pupil Double-Dispersed Spectrograph, and Southern Astrophysical Research; long-term Optical Gravitational Lensing Experiment V - and I -bands photometry dating back to 6 yr before eruption; Small and Moderate Aperture Research Telescope System optical and near-IR photometry from ∼11 d until over 280 d post-eruption; Swift satellite X-ray and ultraviolet observations from ∼6 d until 319 d post-eruption. The progenitor system contains a bright disc and a main sequence or a sub-giant secondary. The nova is very fast with t 2 ≃ 4.0 ± 1.0 d and t 3 ≃ 7.8 ± 2.0 d in the V band. If the nova is in the SMC, at a distance of ∼61 ± 10 kpc, we derive M V, max ≃ −10.5 ± 0.5, making it the brightest nova ever discovered in the SMC and one of the brightest on record. At day 5 post-eruption the spectral lines show a He/N spectroscopic class and an Full Width at Half Maximum of ∼3500 km s −1, indicating moderately high ejection velocities. The nova entered the nebular phase ∼20 d post-eruption, predicting the imminent super-soft source turn-on in the X-rays, which started ∼28 d post-eruption. The super-soft source properties indicate a white dwarf mass between 1.2  and 1.3 M⊙ in good agreement with the optical conclusions.